Abrogation of Article 370: The Symbol of National Integrity - Ahmad, Irshad; Parihar, Dr. Seema (Gyan Management Journal, 2023)
A few specific privileges provided to citizens of the Indian state  of Jammu and Kashmir were recently abolished by the Indian  government. Under Articles 370 and 35A of the Constitution, these  rights were provisionally conferred. The Indian government placed  some limitations on travel and communication in the Kashmir valley  because it anticipates that this step may spark violent protests in the  state. Pakistan has spearheaded a defamation campaign against India  even though these prohibitions have increasingly been loosened. Over  this action, it has even threatened a nuclear exchange. The prime  minister of India Mr Narendra Modi said that more than 70,000 lives  have been lost over the past thirty years as a result of the particular  privileges that the people of Jammu and Kashmir have, which has  led to a sense of difference that has been exploited by forces opposed  to India’s unity. The neighbourhood was not getting any closer to  peace by maintaining the current quo. Hopefully, the elimination of  these articles will result in a stronger sense of national integration.  Therefore in view of the above statements this dissertation paper is  being prepared to study and spread the truth to the all citizens of India  that abrogation of article has ended all kinds of privileges and special  treatments and has paved the way to the national integration of India
Keywords: Article 370; Abrogation; Transport; communications; Symbol; Nation; Unity and integrity